Self-ordering kiosk usage and post-purchase behaviour in quick service restaurant / Noradzhar Baba, Aslinda Mohd Shahril and Mohd Hafiz Hanafiah. - Baba, Noradzhar; Mohd Shahril, Aslinda; Hanafiah, Mohd Hafiz (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Cawangan Selangor, 2020)
This conceptual paper aims to explore the relationship between the customer self-ordering kiosk usage and post-purchase behaviour in quick-service restaurants. The self-ordering kiosk is the latest innovative technology to be offered by restaurants to improve customer experiences, especially in quick-service restaurants. However, the assessments of customers’ actual usage, as well as the question whether it motivates future behavior, have yet to be explored empirically. The Unified Theory of Acceptance and Use of Technology (UTAUT2) is found to be the most adopted model in foodservice and technology studies. To fit with the proposed research framework, the UTAUT2 model was adopted and modified by incorporating post-purchase behaviour that acts as the dependent variable. Seven theoretical propositions are suggested in reference to the literature review. This study serve as an addition to the literature of digital technology and application adoption on the menu-ordering transactions and also the foodservice system.